A new macroazo-initiator for the synthesis of polymers with crown ether units - Yaĝci, Yusuf; Tunca, Ümit; Biçak, Niyazi (Wiley, 1986)
Synthese d'un polyamide a partir de transdiaminodibenzo-4,4 benzo-18 crown-6, amorceur de la polymerisation radicalaire en masse du styrene a 70°C